Christmas in many cultures - Rustad, Martha E. H. (Martha Elizabeth Hillman), 1975- (Mankato, Minn. : Capstone Press, 2009)
Simple text and photographs present how Christmas is celebrated in various countries, including the U.S., Mexico, Ethiopia, Iceland, the Ukraine, Malaysia, South Africa, and Australia.
Includes bibliographical references (p. 23) and index.
2.4
K-3.
K-3
Keywords: Christmas -- Juvenile literature; Christmas; Holidays; Christmas; Holidays; Readers (Elementary).